A NUMERICAL AND EXPERIMENTAL STUDY FOR AERODYNAMIC THRUST OPTIMIZATION - Jane Bulut; Ferhat Karakaş; İdil Fenercioğlu; Ülgen Gülçat (Havacılık ve Uzay Teknolojileri Dergisi, 2016)
Flapping wings draw considerable attention due to their advantages in lift and thrust recovery in low Reynolds number fight, where they can be used as an alternative to conventional micro air vehicle (MAV) designs. The application areas of MAVs has widened with the development of new flight techniques of MAVs besides their advantages that they already have such as lightness, being small in size and quietness. Their lightweight is one of their primary advantages; however the thrust provider systems result in MAVs to get heavier. At this point, flapping wings might have a crucial role in generation of thrust for MAV flight. Thrust generation from flapping wings is inspired from powered flight in nature. In this study, the behavior of a flat plate performing simultaneous pitching and plunging motions is numerically determined for optimum thrust. Then, for 12 different test cases, experimental force measurements are made using an oscillating flat plate with various frequencies and amplitudes, including the optimum, in both zero freestream velocity and with a finite freestream velocity to compare the results. The experimental and numerical results have better agreement at lower frequencies of the airfoil motion. Both the experimental and numerical results show that with increasing motion frequency and amplitude the generated thrust also increases proportionally.